2022
DOI: 10.3390/app12189311
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Methodology to Improve Speaking Skills in English Language Learning Using Mobile Applications

Abstract: The main objective of this research is a working example of how a hybrid methodology combining traditional methodologies and mobile devices can be used to contribute to the literature on mobile learning in teaching English as a second language. This work was carried out because, in many Latin American countries, students are taught English as a second language throughout their primary and secondary education. However, at the end of their studies, most students are unable to communicate with other people in Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…There are several benefits and drawbacks of utilizing mobile applications to learn English based on the previous research and findings of this research (Ameri, 2020;Criollo-C et al, 2022;Kacetl & Klímová, 2019;Kusmaryani et al, 2019). The benefits are mobile applications make it easier for students to practice their English language abilities anywhere and at any time, students can focus on areas where they need to improve by using mobile applications that can be tailored to match their specific needs, students' motivation to learn can rise as a result of mobile applications that can make learning English more interesting and enjoyable, and numerous studies have revealed that using mobile apps can help users remember new terminology.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There are several benefits and drawbacks of utilizing mobile applications to learn English based on the previous research and findings of this research (Ameri, 2020;Criollo-C et al, 2022;Kacetl & Klímová, 2019;Kusmaryani et al, 2019). The benefits are mobile applications make it easier for students to practice their English language abilities anywhere and at any time, students can focus on areas where they need to improve by using mobile applications that can be tailored to match their specific needs, students' motivation to learn can rise as a result of mobile applications that can make learning English more interesting and enjoyable, and numerous studies have revealed that using mobile apps can help users remember new terminology.…”
Section: Discussionmentioning
confidence: 90%
“…Using mobile applications, Criollo-C et al (2022) suggested a hybrid methodology to enhance speaking abilities in English language acquisition. To improve students' speaking abilities, the system makes use of mobile technologies and educational applications.…”
Section: Discussionmentioning
confidence: 99%
“…Two manuscripts of this systematic review are from Spain (Europe) and the rest from Asian countries. Many Latin and Asian countries often use alternative method to improve English as Second Language because of the high demand of English level in sectors as academic, professional or tourism sectors among others (Chen, 2022;Criollo-C. et al, 2022;Hooli et al, 2023;Zečević & Biševac, 2022). TPR and physical activities are motivating methods to improve the EFL learning on higher education students and at the same time, it helps to improve the health and increasing the motivation of students (Fernández-Barrionuevo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the design should ensure that the application generates motivation and intention to use it [47], [48]. The user's perception regarding the use of the application must be pleasant, the navigation between the different interfaces of the game must be easy and intuitive [49], [50]. Each screen must be presented in a coherent way,…”
Section: Requirements Characteristicsmentioning
confidence: 99%